Red : a crayon's story - Hall, Michael, 1954- (Greenwillow Books, an imprint of HarperCollinsPublishers, 2015)
Red's factory-applied label clearly says that he is red, but despite the best efforts of his teacher, fellow crayons and art supplies, and family members, he cannot seem to do anything right until a new friend offers a fresh perspective.